Gaming Gone Viral: An Analysis of the Emerging Esports Narrative Economy. (April 2022) - Newman, Joshua I.; Xue, Hanhan; Watanabe, Nicholas M.; Yan, Grace; McLeod, Christopher M.
In this article, we use narrative economics to analyze the social conditions promoting the growth in private investment in esports—specifically in North American esports teams and franchises. Investment in the esport industry has outpaced revenue growth and esport teams do not have a proven cash flow model. To understand this disjuncture, we draw upon the narrative economic approaches developed by Robert Shiller and colleagues who have demonstrated how the public narrative holds the potential to influence economic behavior—and whereby following a popular story might lead to irrational investment, labor, or consumption practices. We provide a quantitative analysis of published stories that shows the virality of esport narratives is consistent with epidemic models and that business investment narratives are spreading faster than general esport narratives. We then provide a mixed method analysis that demonstrates the central narrative of esport stories is one of growth, opportunity, and sport-esport synergies. We conclude with a discussion about the industrial and theoretical implications of studying viral stories as they relate to preconditioning economic behavior in the sports industry.